Zingiber vuquangense (Sect. Cryptanthium: Zingiberaceae): a new species from North central coast region, Vietnam - Lê, Thị-Hương; Trịnh, Thị-Hương; Ðỗ, Ngọc-Ðài; Nguyễn, Việt-Hùng; Lý, Ngọc-Sâm (Phytotaxa, 2019)
Zingiber vuquangense, a new species of Zingiberaceae, is described and illustrated from North Central Coast region of Vietnam. It is most similar to Z. cornubracteatum, but differs by its smaller plant, longer ligules and petiole, leaf shape, colour of bract, bracteole and flower, and fruit shape. Data on distribution, habitat, vernacular name and uses, a distribution map and a colour plate of the new species are presented.